Analysis of Computer Science Education in Venezuela Using the Darmstadt Model - Fecht, Nubia Alejandra; Diethelm, Ira (Informatics in Schools. Teaching and Learning Perspectives, 2014)
From time to time societies have to change their educational system in order to adapt to new social or economic conditions. This is especially necessary for teaching the subjects CSE and ICT because their scientific background alters very quickly and their relevance grows steadily. Venezuela had to meet this challenge in a way that cannot really be compared with European circumstances because of the political, ideological and regional differences. For this study we went to Venezuela where we conducted several interviews with representatives of the Venezuelan educational system who are involved in Computer Science Education (CSE). The interview data was analyzed using the Darmstadt Model, a model created especially for analyzing the situation of CSE in different countries. It was the first time this model was used to examine the situation of a Latin American country. Our results provide further information to people who have to develop, organize and evaluate CSE and ICT lessons.